Breast tumor PDXs are genetically plastic and correspond to a subset of aggressive cancers prone to relapse. Issue 2 (19th December 2013) - du Manoir, Stanislas; Orsetti, Béatrice; Bras-Gonçalves, Rui; Nguyen, Tien-Tuan; Lasorsa, Laurence; Boissière, Florence; Massemin, Blandine; Colombo, Pierre-Emmanuel; Bibeau, Frédéric; Jacot, William; Theillet, Charles
Abstract : Patient derived xenografts (PDXs) are increasingly appreciated models in cancer research, particularly for preclinical testing, as they reflect the patient's tumor biology more accurately than cancer cell lines. We have established a collection of 20 breast PDXs and characterized their biological and clinical features, as well as their genetic stability. While most PDXs originated from triple negative breast cancers (70%), our collection comprised five ER + cases (25%). Remarkably, the tumors that produced PDXs derived from a subset of aggressive breast cancers with a high proportion of grade 3 tumors and reduced recurrence‐free survival. Consistent with this, we found significant differences between the transcriptomic signatures of tumors that produced a PDX (Take) and those that did not (No Take). The PDXs faithfully recapitulate the histological features of their primary tumors, and retain an excellent conservation of molecular classification assignment and Copy Number Change (CNC). Furthermore, the CNC profiles of different PDXs established from the same tumor overlap significantly. However, a small fraction of CNCs in the primary tumor that correspond to oligoclonal events were gradually lost during sequential passaging, suggesting that the PDXs' genetic structure eventually stabilizes around a dominant clone present in the tumor of origin. Finally, de novo occurring genetic events covering up to 9% of the genome were found in only a minority of the PDXs, showing that PDXs have limited genetic instability. These data show that breast cancer PDXs represent a subset of aggressive tumors prone to relapse, and that despite of an excellent conservation of original features, they remain genetically dynamic elements. Highlights: A collection of breast cancer PDXs is described. PDXs represent a subset of clinically aggressive breast tumors. Most PDXs derive from a dominant genetic subclone present in the tumor of origin. PDXs are genetically dynamic and susceptible to slow drift.